Exploring the role of animal technologists in implementing the 3Rs: An ethnographic investigation of the UK university sector - Greenhough, B; Roe, E (SAGE Publications, 2017)
The biomedical industry relies on the skills of Animal Technologists (ATs) to put laboratory animal welfare into practice. This is the first study to explore how this is achieved in relation to their participation in implementing refinement and reduction, two of the three key guiding ethical principles––the “3Rs”––of what is deemed to be humane animal experimentation. The interpretative approach contributes to emerging work within the social sciences and humanities exploring care and ethics in practice. Based on qualitative analysis of participant observation within animal research facilities in UK universities, in-depth interviews with Animal Technologists, facility managers and other stakeholders, and analysis of regulatory guidelines, we draw a contrast between the minimum required of ATs by law and how their care work not only meets, but often exceeds these requirements. We outline how ATs constitute a key source of innovation and insight into the refinement of animal care and the reduction of animal use, hitherto not formally acknowledged. Exploring AT care work as an example of ethics in practice makes an original contribution to broader debates within healthcare and animal welfare about how technology, regulation and behavior can foster and sustain a culture of care.